The business of prostitution perspectives on legalization and decriminalization - Arcebal, Maxim Jay J.; Crisologo, Dayanne R.; Rodriguez, Lila B. ([Quezon City] [National College of Public Administration and Governance, University of the Philippines Diliman], 2012)
This research explored the business of prostitution and the trends on legalization and decriminalization primarily through the three clusters of research questions: 1) policies on prostitution, 2)proposed bills on prostitution, and 3) stakeholders' perceptions. To answer these questions, the researchers did desk and library research, visited the archives of the Quezon City Hall and the Senate and House of Representatives, and conducted interviews to gather the perception of five stakeholders namely: prostitutes, clients, business operators, law enforcers, and women's groups. The findings of the researchers on the policies, proposed bills, and stakeholders' perceptions, using the lens of ethic of care, would show that the country is generally not willing to legalize prostitution in the country although moves to decriminalize prostitutes have been successful.
Thesis (Public Administration)--University of the Philippines, Diliman
Includes bibliographical references
Keywords: Prostitution -- Law and legislation -- Philippines; Sex-oriented businesses -- Law and legislation -- Philippines